2002
DOI: 10.1103/physrevlett.89.285506
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-Beam Deposition andin situCharacterization of Carbyne-Rich Carbon Films

Abstract: Nanostructured carbon films produced by supersonic cluster beam deposition have been studied by in situ Raman spectroscopy. Raman spectra show the formation of a sp2 solid with a very large fraction of sp-coordinated carbyne species with a long-term stability under ultrahigh vacuum. Distinct Raman contributions from polyyne and cumulene species have been observed, as well as different stabilities under gas exposure. Our experiments confirm theoretical predictions and demonstrate the possibility of producing a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
194
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(216 citation statements)
references
References 28 publications
17
194
0
5
Order By: Relevance
“…Cumulene-like structures have been observed together with polyynes in a pure sp-sp 2 -carbon cluster-assembled system. 27,88 It has been observed that the cumulene fraction has a higher tendency to undergo transformation to sp 2 -carbon structures, confirming reduced stability toward oxygen exposure and high temperatures. 98,116,117 Different terminations that can be provided by the amorphous carbon network can produce cumulene or polyyne structures, respectively.…”
Section: Synthesis and Preparation Of Sp-carbon Systems: A Brief Overmentioning
confidence: 98%
See 1 more Smart Citation
“…Cumulene-like structures have been observed together with polyynes in a pure sp-sp 2 -carbon cluster-assembled system. 27,88 It has been observed that the cumulene fraction has a higher tendency to undergo transformation to sp 2 -carbon structures, confirming reduced stability toward oxygen exposure and high temperatures. 98,116,117 Different terminations that can be provided by the amorphous carbon network can produce cumulene or polyyne structures, respectively.…”
Section: Synthesis and Preparation Of Sp-carbon Systems: A Brief Overmentioning
confidence: 98%
“…1,21 Nowadays the occurrence of sp-hybridized carbon has been suggested in many carbon-based materials and structures, in carbon-metal moieties, embedded in matrices, after laser irradiation of polymers, in free carbon clusters, in pure sp-sp 2 systems, in liquids, inside carbon nanotubes (CNTs) and connecting graphene sheets. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] In addition, synthetic strategies allow us to produce long and stable sp-carbon wires with controlled length and termination. 36 Theoretical investigations have predicted a number of interesting vibrational, electronic, and transport properties that can be tuned by controlling the wire length and endgroups.…”
Section: S Casarimentioning
confidence: 99%
“…The enhanced band at 1900-2300 cm −1 can be identified with sp-bonded carbon chains. 3,5 The presence of sp 3 -bonded species is also indicated by the appearance of a T band centered at 1050 cm −1 ͑Ref. 15͒.…”
mentioning
confidence: 99%
“…19 SERS spectra of central irradiated areas show that peaks at 1960 and 2095 cm −1 can be identified with cumulenes ͑C v C͒ n and polynes ͑-C w C-͒ n , respectively. 3,12 The presence of a diamond component can be seen in the lightly ablated area, which displays a band at 1260 cm −1 due to tetrahedral carbon 20 diamond at the L point. 21 Trans-polyacetylene chains having different lengths are identified by the presence of several modes at 1150, 1190, and 1450 cm −1 .…”
mentioning
confidence: 99%
“…Samples of pure carbon films grown by supersonic cluster beam deposition at room temperature have been characterized, and proven to contain a sizeable sp component [23,24]. These spCCs showed weaker stability relative to the sp 2 component upon exposition to low pressure gases at room temperature [25].…”
Section: Introductionmentioning
confidence: 99%